Direct observation of V-trimers in the crystal structure of LiVO2 - S. Yun; C.-F. Chang; S.-H. Chen; C.-Y. Kuo; L. H. Tjeng; A. C. Komarek (Communications Chemistry)
Abstract Although a trimerized ground state has been predicted for LiVO2 for over half a century, the direct determination of its crystal structure in the trimerized phase by X-ray diffraction remains elusive. Depending on the cooling process, two distinct structural modifications have been prepared - LiVO2 with streak-like, smeared-out superstructure reflection intensities and Li0.91VO2 with well-separated superstructure reflection intensities. The discovery of well-separated superstructure reflections in Li0.91VO2 enabled us to solve its crystal structure. This motivated us to attribute the streak-like superstructure reflection intensities in LiVO2 to an overlap of reflections due to a unit cell doubling along the c-axis, which contrasts with the previous interpretation of randomly stacked V trimer layers. The availability of the crystal structure data forms a starting point for the quantitative modeling of the trimerization phenomenon in this complex Mott insulator.